"Bahasa Inggris" Textbook for The Eleventh Grade: Its Readability and Teacher's HOTs Teaching Strategies - Khalif Al Bilal, - (2022)
The readability of a textbook is an essential consideration in ensuring the students' understanding of the materials contained in the textbook. A textbook with the right level of readability could facilitate better understanding and thus optimize learning. In addition, teaching reading with Higher Order Thinking Skills (HOTS) techniques could also be highly beneficial for improving students' reading performance. However, teachers often choose a textbook for granted and struggle to implement HOTS teaching strategies. Therefore, it is urgent to analyze the selected textbook's readability level before giving it to students and teaching strategies to develop students' reading performance. The study analyzed the eleventh grade 'Bahasa Inggris' textbook and recruited 140 eleventh graders from 4 classes and an English teacher from a senior high school in Bandung as the participants. The data analysis involved analyzing the readability level of reading materials using readability formulas and cloze test; analyzing the questionnaires and interviews with the students; and correlating the discrepancy of perceptions among the formulas' results, teacher's HOTS teaching strategies and the students. The results indicated that only one text is appropriate to the target reader, while other texts are one level above and two-level below eleventh grade. The teaching with HOTS strategies in reading utilized by the teacher in which to teach reading helps the student understand the texts better and develop their critical thinking, making the students could read various levels of readability.